«АҚМАҚ ПАТША» ДӘСТАНЫНДА ФОЛЬКЛОРЛЫҚ МОТИВЛЕРДИҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИГИ - Жәримбетов, Қ.; Палымбетова, М. (ILIM hám JÁMIYET, 2016)
The article is devoted to the study of using folklore motives in the epos «Stupid king» by Berdakh in the description of life truth.